Prevalence and Predictors of Perpetration of Cyberviolence Against a Dating Partner: A Cross-Cultural Study with Moroccan and Spanish Youth - Soriano-Ayala, Encarnación (Journal of interpersonal violence, 2023)
The rise in the levels of cyberviolence in adolescent couples has become a social, educational, and public health problem of enormous magnitude. This study analyzed the nature and dimensions of cyberviolence among adolescents and its association with other forms of offline violence by country of origin (Morocco or Spain) and gender. The objective of the study was to identify the predictors of the perpetration of cyberviolence against a dating partner. The predictor variables were five types of dating victimization (cyber, physical, sexual, emotional with a social impact, and emotional with an individual impact), history of violence, and parental monitoring knowledge. The sample consisted of Spanish (n = 802) and Moroccan students (n = 241) who had dated and attended secondary schools in southeastern Spain. Over half of the participants had perpetrated cyberviolence against their partners; the prevalence was higher among girls and Moroccan youth. Boys reported more physical victimization than girls. For all groups, the strongest predictor of cyberviolence perpetration was cyberviolence victimization. The influence of other forms of victimization, history of offline violence, and parental monitoring differed by the youth’s country of origin and gender. The study reinforces the need for intersectional and cross-cultural analyses of online behaviors.